Hemodynamic Comparison of Stent-Grafts for the Treatment of Aortoiliac Occlusive Disease. (August 2021) - Chong, Albert; Mirgolbabaee, Hadi; Sun, Zhonghua; van de Velde, Lennart; Jansen, Shirley; Doyle, Barry; Versluis, Michel; Reijnen, Michel M. P. J.; Groot Jebbink, Erik
Purpose: To compare the flow patterns and hemodynamics of the AFX stent-graft and the covered endovascular reconstruction of aortic bifurcation (CERAB) configuration using laser particle image velocimetry (PIV) experiments. Materials and Methods: Two anatomically realistic aortoiliac phantoms were constructed using polydimethylsiloxane polymer. An AFX stent-graft with a transparent cover made with a new method was inserted into one phantom. A CERAB configuration using Atrium's Avanta V12 with transparent covers made with a previously established method was inserted into the other phantom, both modified stent-grafts were suitable for laser PIV, enabling visualization of the flow fields and quantification of time average wall shear stress (TAWSS), oscillatory shear index (OSI), and relative residence time (RRT). Results: Disturbed flow was observed at the bifurcation region of the AFX, especially at the end systolic velocity (ESV) time-point where recirculation was noticeable due to vortical flow. In contrast, predominantly unidirectional flow was observed at the CERAB bifurcation. These observations were confirmed by the quantified hemodynamic results from PIV analysis where mean TAWSS of 0.078 Pa (range: 0.009–0.242 Pa) was significantly lower in AFX as compared with 0.229 Pa (range: 0.013–0.906 Pa) for CERAB (p<0.001). Mean OSI of 0.318 (range: 0.123–0.496) in AFX was significantly higher than 0.252 (range: 0.055–0.472) in CERAB (p<0.001). Likewise, mean RRT of 180 Pa −1 (range: 9–3603 Pa −1 ) in AFX was also significantly higher than 88 Pa −1 (range: 2–840 Pa −1 ) in CERAB (p=0.0086). Conclusion: In this in vitro study, the flow pattern of a modified AFX stent-graft was found to be more disturbed especially at the end systolic phase, its hemodynamic outcomes less desirable than CERAB configuration. Clinical Relevance: While the AFX stent-graft has an advantage over the CERAB configuration in eliminating radial mismatch, and maintaining the anatomical bifurcation for future endovascular intervention, this in vitro study revealed that the associated lower TAWSS, higher OSI and RRT may predispose to thrombosis and are, thus, less desirable as compared to a CERAB configuration. Further investigation is warranted to confirm whether these findings translate into the clinical setting.